2018
DOI: 10.3390/batteries4030032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of La3+ Modification on the Electrochemical Performance of Na3V2(PO4)2F3

Abstract: La 3+ modification of Na 3 V 2 (PO 4) 2 F 3 was performed by the direct mechanochemically assisted solid-state synthesis of the Na 3 V 2−x La x (PO 4) 2 F 3 compositions, and by the LaPO 4 coating of the as-prepared Na 3 V 2 (PO 4) 2 F 3 via the precipitation method. It has been shown that no noticeable substitution of the V 3+ ions by the La 3+ ions occurs in the Na 3 V 2 (PO 4) 2 F 3 structure under the synthesis conditions; meanwhile, the introduction of the La 3+ ions into the reagent mixture leads to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Kosova et al have demonstrated that Lanthanum substitution was in fact a surface modification effect by LaPO4. 15 The group of Ceder has studied gallium and aluminium substitution for vanadium, with the aim to disrupt the charge and Na + orderings within the lattice and thus lower the energy barrier for the reversible extraction of the 3 rd Na. 16,17 Among the different metals, aluminium drew our attention as Al is cheaper, lighter, more environmentally friendly than V and, as a nonelectrochemically active element, could participate to the stabilization of the material upon cycling.…”
mentioning
confidence: 99%
“…Kosova et al have demonstrated that Lanthanum substitution was in fact a surface modification effect by LaPO4. 15 The group of Ceder has studied gallium and aluminium substitution for vanadium, with the aim to disrupt the charge and Na + orderings within the lattice and thus lower the energy barrier for the reversible extraction of the 3 rd Na. 16,17 Among the different metals, aluminium drew our attention as Al is cheaper, lighter, more environmentally friendly than V and, as a nonelectrochemically active element, could participate to the stabilization of the material upon cycling.…”
mentioning
confidence: 99%